2017
DOI: 10.1177/1369148117718461
|View full text |Cite
|
Sign up to set email alerts
|

Social media and youth political engagement: Preaching to the converted or providing a new voice for youth?

Abstract: Amidst concern about declining youth political engagement, it is often suggested that social media can provide a solution to this challenge. In this article, however, we argue that these online tools have not thus far mobilised a new audience to become engaged in either institution-oriented activities or political expression. Instead, we found that some young people are far more engaged in using social media for political purposes than others, and that a substantial proportion of young adults never use social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 43 publications
1
47
1
5
Order By: Relevance
“…Existing literature reviewed for the study but any questionnaire was not applied literally. While questionnaire preparing, studies benefited from are Dordevic and Zezelj (2016), Keating and Melis (2017), Metzger, Erete, Barton and Lewis (2015) and Pritzker, Springer and McBride (2012) for the survey. The preliminary survey was made for the efficiency of the content and the sufficiency for the analysis on ten students and then questionnaire was applied to 320 students using convenience sampling willingly participated from different faculties.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing literature reviewed for the study but any questionnaire was not applied literally. While questionnaire preparing, studies benefited from are Dordevic and Zezelj (2016), Keating and Melis (2017), Metzger, Erete, Barton and Lewis (2015) and Pritzker, Springer and McBride (2012) for the survey. The preliminary survey was made for the efficiency of the content and the sufficiency for the analysis on ten students and then questionnaire was applied to 320 students using convenience sampling willingly participated from different faculties.…”
Section: Methodsmentioning
confidence: 99%
“…During this life-stage, young citizens have less of the resources (time, money or mental energy) that are believed to be prerequisites to political engagement (Verba, Schlozman and Brady 1995). However, as online participation requires fewer resources (financial or otherwise), it has been suggested that these online tools could help to compensate for the resource limitations that young adults face and provide a low-cost site for engagement (Keating and Melis 2017). In the case of young people, the creative effect of the Internet is more prominent.…”
Section: Youth Participationmentioning
confidence: 99%
“…It is observed that European formal citizenship education does not promote civic activism (Biesta, 2009). In the same vein, Ribeiro and her colleagues (2012, p. 32) On the other hand, it is noteworthy to see that unlike the common sense view, social media use does not boost political engagement, as those using social media for political purposes are the ones that are already political in their real lives (Keating & Melis, 2017). Kara's (2018, p. 172) findings are even more pessimistic: "students indicated that they do not prefer to engage in political activities online because of emotional disturbance, pressure from society, and a fear of affecting their future lives in a negative way. "…”
Section: Data Activism and Critical Citizenship Educationmentioning
confidence: 99%
“…Some scholars only report engaged and disengaged participators [ 23 , 24 ], others all-round activists, high-voting engaged, mainstream and disengaged participants [ 22 , 41 ], or agitators, outsiders, activists, and conventionals [ 16 ]. A study on youth online participation identifies engagers and non-engagers [ 42 ].…”
Section: Political Participant Types and Personalitymentioning
confidence: 99%
“…Links have been established between age, socio-economic status, education, and political knowledge [ 16 , 19 , 23 , 41 ]. Furthermore, recent research suggests that political interest appears to be the principal driver for youth engagement [ 42 ]. Factors beyond the traditional socio-economic model plus political involvement have not been studied in relation to participant typologies yet.…”
Section: Political Participant Types and Personalitymentioning
confidence: 99%